Effect of helium implantation on the hydrogen retention of Cr2O3 films formed in an ultra-low oxygen environment. (8th October 2019) - Zhou, Qingyun; Ling, Yunhan; Lu, Zhaoxia; Zhang, Mengyuan; Zhang, Zhengjun; Xiao, Tian; Wang, Rongguang
Abstract: To simulate and investigate the irradiation damage of neutron and transmutation effect (He production) on the hydrogen isotope trapping behavior, in the present study, a new monoclinic hydrogen permeation barrier composed of Cr2 O3 was fabricated and helium implantation with different fluences was tentatively employed. First, pure chromium samples were oxidized in an ultra-low oxygen partial pressure (1.7 × 10 −23  Pa) environment to obtain a single Cr2 O3 layer. Then a dense layer of helium bubbles was formed in a substrate using a helium ion implantation method. Finally, the samples were treated in a hydrogen plasma environment at 500 °C. The damage, vacancy, and helium distribution in these samples were then simulated by SRIM. The morphology, phase, surface characteristics, thermal desorption, and electrochemical properties were subsequently characterized and evaluated. Thermal desorption spectrum analysis (TDS) was used to study the thermal desorption of hydrogen and helium at different temperatures. Our results showed that the inhibitory effect of the composite hydrogen barrier layer on the hydrogen diffusion in the substrate first increased and then decreased with the increase of the helium ion implantation fluence. Graphical abstract: Image 1 Highlights: A dense Cr2 O3 film was successfully fabricated in an ultra-low O2 environment. Helium was implanted to investigate its defect and trapping behavior. Results indicated that helium has significant effect on hydrogen retention.